Portfolio optimization of energy commodity futures returns: Vine copula approach - Payap Tarkhamtham (2018)
© Serials Publications Pvt.Ltd. The objectives of this study are to construct the optimum energy commodity portfolio investment by using Vine-copula GARCH, and to quantify their risk with Value-at-Risk and expected shortfall. The 1,979 energy commodity futures prices from 7 energy commodity products, namely crude oil, natural gas, gasoline, heating oil, diesel, ethanol, and gasoil, were collected from 1 September 2009 to 31 March 2017, traded in the New York Mercantile Exchange (NYMEX). The empirical results showed that every fitted conditional volatility models are ARMA-EGARCH with student t, and skew student t distribution, and the appropriate vine-copula model for dependence structure among three types of vine copulas is C-vine. The estimated VaR and ES of the portfolio in period t+1at 10%, 5%, and 1% level are-2.33,-3.12,-4.81 and-3.54,-4.40,-3.54 respectively. The optimum portfolio investment result suggests to focuses on the diesel, ethanol, and gas oil investment due to high investment proportion, whereas crude oil and gasoline have little investment proportion.